Synthesis and Characterization of Polyester Thin Film Composite Membrane via Interfacial Polymerization: Fouling Behaviour of Uncharged Solute - Mah, K. H.; Wan Mohd Hafizuddin, Wan Yussof; Mazrul Nizam, Abu Seman; A. W., Mohammad (IOP Publishing Ltd, 2017)
Most hydrolysis studies on biomass in Malaysia produce high amount of xylose and glucose compared to other monosaccharides and most of them are acidic. Thin film composite (TFC) membrane developed via interfacial polymerization using triethanolamine (TEOA) and trimesoyl chloride (TMC) as monomers allows separation at low pH to occur without damaging its performance. Comparative studies were carried out on membranes with and without the thin film layer formed via interfacial polymerization on the polyethersulfone (PES) support. The surfaces of the membranes were characterized by field emission scanning electronic microscopy (FESEM), attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, and hydrophilicity via contact angle measurement. In addition, the performance and uncharged solute fouling behaviour of TFC membrane were also investigated. The TFC membrane used for characterization purposes was prepared at TEOA concentration of 4 % w/v in 1 × 10-6 M sodium hydroxide solution, TMC concentration of 0.25 % w/v in pure hexane, reaction time of 45 minutes, and cured at temperature of 60 °C. Characterization results showed a huge different between the synthesized TFC membrane and the un-synthesized PES membrane in term of surface properties and morphology. Nanofiltration results indicate that the formation of thin layer on top of PES support membrane improved the separation performance compared to PES support membrane. The synthesised polyester TFC membrane have irreversible fouling of 11.02 (±5.60) % and reversible fouling of 5.59 % using water as cleaning agent.